2017
DOI: 10.1002/anie.201705924
|View full text |Cite
|
Sign up to set email alerts
|

Re2O7‐Mediated Dehydrative Cyclization Reactions: Total Synthesis of Herboxidiene and Its 12‐Desmethyl Analogue

Abstract: Re2O7 catalysis effects efficient and stereoselective dehydrative cyclization reactions from monoallylic diols, with stereocontrol arising from thermodynamic equilibration. This method was applied to a rapid synthesis of the spliceosome inhibitor herboxidiene. The route was also utilized for the synthesis of an analog that highlights the importance of a single methyl group in biasing the conformation in the acyclic region of the molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…This reaction initially generates a mixture of diastereomers that converged to the thermodynamically preferred product after gentle heating. 30 Qi Qin demonstrated numerous examples of this experimentally facile and atom-economical cyclization process. Highlights among these include the conversion of triol 55 into 56, in which each hydroxy group serves a different role (one as a nucleophile, one as a leaving group, and one as a spectator), and the transformation of 57 into 58, in which the presence of an additional stereocenter in the product is not detrimental to the cyclization efficiency.…”
Section: Development Of Dehydrative Cyclizationsmentioning
confidence: 99%
“…This reaction initially generates a mixture of diastereomers that converged to the thermodynamically preferred product after gentle heating. 30 Qi Qin demonstrated numerous examples of this experimentally facile and atom-economical cyclization process. Highlights among these include the conversion of triol 55 into 56, in which each hydroxy group serves a different role (one as a nucleophile, one as a leaving group, and one as a spectator), and the transformation of 57 into 58, in which the presence of an additional stereocenter in the product is not detrimental to the cyclization efficiency.…”
Section: Development Of Dehydrative Cyclizationsmentioning
confidence: 99%
“…The cytotoxic evaluation against HeLa cells revealed that the absence of the C12 methyl group induced at least a 40-fold drop in potency relative to herboxidiene. [76] A carbohydrate-derived analogue (91) was active in CLL-B cells (IC 50 = 153.0 nM) with~3-fold reduction of activity as compared to FD-895 (IC 50 = 54.1 nM). Compound 91 also exerted the effects on inducing intron retention and modulating alternative splicing in CLL-B cells, which was comparable to that of FD-895.…”
Section: Sar Of Monopyranesmentioning
confidence: 99%
“…Floreancig group fulfilled the synthesis of C12 desmethylherboxidiene ( 90 ). The cytotoxic evaluation against HeLa cells revealed that the absence of the C12 methyl group induced at least a 40‐fold drop in potency relative to herboxidiene [76] . A carbohydrate‐derived analogue ( 91 ) was active in CLL‐B cells (IC 50 =153.0 nM) with ∼3‐fold reduction of activity as compared to FD‐895 (IC 50 =54.1 nM).…”
Section: Discovery and Structure‐activity Relationships Of Small‐molementioning
confidence: 99%
“…Our studies in the applications of Re 2 O 7 to allylic alcohol transposition reactions5,6 resulted in a new dehydrative cyclization protocol in which allylic cations react with pendent hydroxy groups 7,8. Re 2 O 7 proved to be superior to Brønsted acids for promoting these processes, leading us to speculate that it could be an effective catalyst for enabling bimolecular dehydrative coupling reactions.…”
Section: Introductionmentioning
confidence: 97%